MENINGKATKAN PRODUKSI KACANG ASIN DENGAN MESIN SANGRAI SEMI OTOMATIS - IK ADI ATMIKA; AA ISTRI AGUNG SRI KOMALA DEWI; TG TIRTHA NINDHIA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
UD Mekar Sari and Bina Sejahtera group is facing a lot of problems to make their product, among others :1) Oven Processing use the rolling machine which is relative modestly with small capacity. 2)Packing productwhich is manually done l by hand and use the candle to gum the plastic packer. 3)Mixturing flavour is also stillmanual so that is less flatten. Planning and making two semi-automatically machine dry-frying in order to havemore amount and better results compared to the appliance use conventional machine. This was also giving theknowledge of appliance, working safety and operation of quality product. The Community service started fromtechnical scheme and appliance making machine, then activity in field executed at 09 November 2013 for therecognition of appliance demonstration and also working safety recognition. This activity was conducted in desaBaluk, kabupaten Jembrana attended by 16 competitive people from various participants, among others : groupmember of Bina Sejahtera, team of community service, students of Mechanical Enginering Departement ofUniversity Udayana, some members from local society. The same activity, moreover was done in UD Mekar Sarion 12 November 2013.Keywords: UD Mekar Sari, Bina Sejahtera group, oven processing, small capacity